When the going gets tough: Power affects the process of making tough decisions. - Li, Xiaoming; Chen, Chuansheng; Zhou, Xin; Ding, Daoqun (Journal of Social Psychology, 2022)
Powerful roles often require individuals to cope with impactful, complicated decisions. The present article reports two experiments investigating the effect of manipulated power mindset on the process of decision-making under different conditions: high vs. low choice conflict (Exp. 1) or high vs. no cognitive load (Exp. 2). Results showed that under the high-choice conflict and high-cognitive load conditions, high-power participants were more likely than low-power participants to take less time, adopt an alternative-based (rather than attribute-based) strategy, rate the tasks as easier, and report higher confidence in and satisfaction with their decisions. Power had no effect on the decision-making process under the low-choice conflict and no-cognitive load conditions. These results suggest that power interacts with choice difficulty to affect the decision-making process.